Land Degradation Surveillance Framework (LSDF): field guide - Vågen, Tor-Gunnar; Winowiecki, Leigh Ann; Walsh, Markus G.; Tamene, Lulseged D.; Tondoh, Jérôme E. (2010)
The field methods employed in the soil health component of the AfSIS (Africa Soil Information Service) project are referred to as the Land Degradation Surveillance Framework (LDSF). This field guide outlines field protocols for measuring indicators of the “health” of an ecosystem, including vegetation cover, structure and floristic composition, historic land use, visible signs of soil degradation, and soil physical characteristics. It is designed to provide a biophysical baseline at landscape level, and a monitoring and evaluation framework for assessing processes of land degradation and the effectiveness of rehabilitation measures over time.